1999
DOI: 10.1046/j.1439-0310.1999.00419.x
|View full text |Cite
|
Sign up to set email alerts
|

Oviposition Site Choice in the Yellow Dung Fly Scathophaga stercoraria

Abstract: Female yellow dung flies Scathophaga stercoraria oviposit on the dung surface, which is extremely uneven and other eggs are often already present. We examined the effects of these features on egg placement. We found that: 1. females preferred to lay on small hills on the dung surface and avoided depressions and points; and 2. they ignored the presence of other eggs. These results were confirmed in a field experiment, where the pattern of egg distribution on artificially formed dung pats was consistent with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 16 publications
0
12
0
1
Order By: Relevance
“…The success of dung fly eggs depends on the topography and microclimate of the place of oviposition on the dropping; choice of a suitable oviposition site increases female reproductive success (Ward et al 1999). Ward (1998) raised larvae of different phosphoglucomutase ( pgm) genotypes in two different dung conditions with the same means for humidity and temperature, but in one set the temperature remained constant and in the other set it was variable.…”
Section: Studies On Sperm Selection By Femalesmentioning
confidence: 99%
“…The success of dung fly eggs depends on the topography and microclimate of the place of oviposition on the dropping; choice of a suitable oviposition site increases female reproductive success (Ward et al 1999). Ward (1998) raised larvae of different phosphoglucomutase ( pgm) genotypes in two different dung conditions with the same means for humidity and temperature, but in one set the temperature remained constant and in the other set it was variable.…”
Section: Studies On Sperm Selection By Femalesmentioning
confidence: 99%
“…Females prefer to lay their eggs on small hills on the dung surface and avoid depressions and sharply elevated points where eggs may suffer a higher risk of drowning or desiccation, respectively, and such female choice of suitable oviposition sites increases female reproductive success . Although Ward et al (1999) found that oviposition was not influenced by the presence of other eggs, a recent study reported that females do respond to egg density by decreasing clutch size on crowded pats (Buser et al unpublished). Intriguingly, females seem not only to choose where to lay their eggs, and how many eggs to lay, but also the parentage of those eggs.…”
Section: Introductionmentioning
confidence: 97%
“…Several authors (Zvereva & Zhemchuzhina, 1985;Hogsette & Washington, 1995;Ward et al, 1999) report that female flies can be very choosy about where they oviposit with marked preferences for particular substrates. The oviposition sites selected are frequently those that are most favourable for larval development .…”
Section: Introductionmentioning
confidence: 99%